Equações algébricas no ensino médio: história, resolução numérica e tecnologia educacional - Abbeg, Thiago Phelippe (2014)
The Algebraic Equations subject are studied in the High School. Basically, the students learn that, if the equation has rational solution then this will belong to a set that can be established. However, if the equation has some irrational root, no method is approached. Furthermore, because the examples are all practiced with equation with rational roots, many students complete the basic cycle believing that we can solve any equation using the algorithm of Briot-Ruffini. In order to complete this gap left in the student’s formation, this work proposes a broader approach to the study of Algebraic Equations, which combines three ingredients: historical overview of the issue, implementing a simple and effective numerical method (of the Bisection) and use of Educational Technology provided by GeoGebra.